2019
DOI: 10.1103/physrevmaterials.3.121201
|View full text |Cite
|
Sign up to set email alerts
|

Defects in Cd3As2 epilayers via molecular beam epitaxy and strategies for reducing them

Abstract: Molecular beam epitaxy offers an exciting avenue for investigating the behavior of topological semimetal Cd3As2, by providing routes for doping, alloying, strain engineering, and heterostructure formation. To date, however, minimal exploration has been devoted to the impact of defects that are incorporated into epilayers due to contraints imposed by the substrate and narrow growth window. Here, we use a combination of lattice-matched ZnxCd1-xTe buffer layers, miscut substrates and broadband illumination to stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…2(a) originates in a largely enhanced scattering that outweighs the expected increase in carrier mobilities due to the formation of bulk Dirac points and the gain in the charge carriers from self-doping. We note that studies on Cd 3 As 2 epilayers revealed a substantial effect of extended defects on electron mobilities [59]. Moreover, for epitaxial (112) Cd 3 As 2 films, a systematic decrease in Hall mobilities with the compressive in-plane strain ( s 0.5%) was observed [24].…”
Section: Discussionmentioning
confidence: 70%
“…2(a) originates in a largely enhanced scattering that outweighs the expected increase in carrier mobilities due to the formation of bulk Dirac points and the gain in the charge carriers from self-doping. We note that studies on Cd 3 As 2 epilayers revealed a substantial effect of extended defects on electron mobilities [59]. Moreover, for epitaxial (112) Cd 3 As 2 films, a systematic decrease in Hall mobilities with the compressive in-plane strain ( s 0.5%) was observed [24].…”
Section: Discussionmentioning
confidence: 70%
“…[13] High-quality thin films of Cd 3 As 2 have been grown by molecular beam epitaxy (MBE) and epitaxial integration of high-mobility Cd 3 As 2 films with III-V semiconductors has been demonstrated. [14][15][16] Despite this progress, the potential of 3D topological semimetals for high-speed electronics remains underexplored. [17,18] In this Article, we model the frequency performance of transistors with Cd 3 As 2 channels, using our experimental measurements of contact resistances, carrier velocities and sheet carrier densities as input parameters.…”
mentioning
confidence: 99%
“…Thus, we infer that the unexpected increase in resistivity after returning to the low pressure regime below P c↓ shown in Figure 2(a) originates in a largely enhanced scattering that outweighs the expected increase in carrier mobilities due to the formation of bulk Dirac points and the gain in the charge carriers from self-doping. We note that studies on Cd 3 As 2 epilayers revealed a substantial effect of extended defects on electron mobilities [52]. Moreover, for epitaxial (112) Cd 3 As 2 films a systematic decrease in Hall mobilities with the compressive in-plane strain ( s 0.4%) was observed [53].…”
Section: Discussionmentioning
confidence: 68%